Extracellular Synthesis of Silver Nanoparticles by Marine Thermophilic Bacteria - S Maruthamuthu, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Extracellular Synthesis of Silver Nanoparticles by Marine Thermophilic Bacteria